1997
DOI: 10.1128/iai.65.9.3644-3647.1997
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of nitric oxide-dependent killing of Mycobacterium bovis BCG in human alveolar macrophages

Abstract: We demonstrated that products of the L-arginine-dependent pathway of human alveolar macrophages (AM) effectively kill the Mycobacterium bovis bacillus Calmette-Guérin (BCG) in vitro. The formation of products was triggered by inoculation with BCG itself. Many reports have shown that activated rodent AM could produce an amount of nitric oxide (NO) sufficient to suppress the growth of mycobacteria. However, there have been no definitive results as to whether human AM might have the NO-dependent mechanism for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
64
0
1

Year Published

1998
1998
2009
2009

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(66 citation statements)
references
References 31 publications
1
64
0
1
Order By: Relevance
“…The annealing temperature for iNOS was 54°and for IL-8 and b-actin it was 65°and 66°, respectively. 35,36 The RT-PCR products were run and visualized on 1AE5% agarose gel with ethidium bromide along with the 100 base pair marker (MBI fermentas; Genetix Biotech Asia Pvt Ltd, New Delhi, India).…”
Section: No Assaymentioning
confidence: 99%
“…The annealing temperature for iNOS was 54°and for IL-8 and b-actin it was 65°and 66°, respectively. 35,36 The RT-PCR products were run and visualized on 1AE5% agarose gel with ethidium bromide along with the 100 base pair marker (MBI fermentas; Genetix Biotech Asia Pvt Ltd, New Delhi, India).…”
Section: No Assaymentioning
confidence: 99%
“…3 However, it has been reported that M. bovis BCG is killed by a NO-dependent mechanism in alveolar macrophages isolated from patients with pulmonary ®brosis. 15 In the bovine system, iNOS activity and NO production has been measured in alveolar macrophages as well as bone marrow, and peripheral blood monocyte-derived macrophages. 12,16,17 Pre-treatment of alveolar macrophages with IFN-c has been shown to limit intracellular growth of M. bovis BCG.…”
Section: Introductionmentioning
confidence: 99%
“…Nitric oxide synthase is known to play an essential role in controlling intracellular persistence and multiplication of B. pseudomallei via the production of nitric oxide [6]. Researchers have shown that suppression of iNOS expression contributed to the progression of infection [15] and enhanced expression of iNOS was demonstrated to be useful in killing intracellular pathogens like Salmonella [16] and Mycobacterium [17].…”
Section: Nitric Oxidementioning
confidence: 99%